Disputed aspects of the reputation management implementation - Shkromyda, Vitaliy (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The recognition of the company and its products, its positive perception among stakeholders are important drivers of sustainable development, which together generate constant sales, provide high margins and strengthen competitive positions in the relevant market. The key factor in this success is the company’s impeccable corporate reputation, the importance and role of which is more and more attested by the researchers in their publications, both on the theoretical and practical levels. Reputation management as a separate component of the company’s governance system is accompanied by debatable issues regarding its separation and independence. The sources on this subject trace differing views among scholars and practitioners to be agreed. Some researchers attribute reputation management to the “public relations” and “corporate relations” competencies and, while others single out and prove its independence as a separate management system, which has its own purpose and specific tasks. The study proved that reputation management is an independent component of the company’s governance system. The substantiation of such a statement is revealed by the essential content of corporate reputation, is accompanied by the clearly outlined goal and performed functions, as well as the justification of the importance of reputation management in the company’s activities and its strategic development. We agree that reputation management is deeply integrated with other components of the governance system, such as “public relations”, “corporate communications” and “corporate relations”, as a result of which they are often equated. However, these components of the governance system differ from each other both in content and purpose. It is established that the highest goal of reputation management is to build a corporate reputation and achieve the key stakeholders’ loyalty. The scientific value of the research is to supplement the theoretical and methodological basis of reputation management, in particular in terms of addressing the disputed aspects of its implementation in the companies’ activities.